Mechanical Properties of Glass Bead- and Wollastonite-Filled Isotactic-Polypropylene Composites Modified With Thermoplastic Elastomers - DEMİRER, HALİL (JOHN WILEY & SONS INC, 2010)
Mechanical properties of the isotactic-polypropylene/glass bead (iPP/GB) and iPP/wollastonite (iPP/W) composites modified with thermoplastic elastomers, the poly(styrene-b-ethylene-co-butylene-b-styrene) copolymer (SEBS) and corresponding block copolymer grafted with maleic anhydride (SEBS-g-MA), were investigated. An increase in toughness of iPP with the elastomers was associated with a decrease in rigidity and strength. Mechanical performance of iPP increased more with acicular W than with spherical GB due to reinforcing effect of W. Comparing the (iPP/GB)/SEBS and (iPP/W)/SEBS composites having the separate microstructure, strength and toughness values of the iPP/GB and iPP/W composites increased more with SEBS-g-MA at the expense of rigidity due to the core-shell microstructure with strong interfacial adhesion. Moreover, the iPP/W composite exhibited superior mechanical performance with 2.5 and 5 vol% of SEBS-g-MA because of a positive synergy between the core-shell microstructure and reinforcing effect of acicular W. The extended models revealed that the elastomer and filler particles in the (iPP/GB)/SEBS and (iPP/W)/ SEBS composites acted individually due to the separate microstructure. However, the rigid GB and W particles encapsulated with the thick elastomer interlayer (R(0)/R(1) = 0.91) in the (iPP/GB)/SEBS-g-MA and (iPP/W)/ SEBS-g-MA composites acted like neither big elastomer particles nor like individual rigid particles, inferring more complicated failure mechanisms in the core-shell composites. POLYM. COMPOS., 31:1285-1308, 2010. (C) 2010 Society of Plastics Engineers
Keywords: FUNCTIONALIZED BLOCK COPOLYMERS; WOOD FLOUR COMPOSITES; RUBBER PARTICLE-SIZE; G-MA ELASTOMERS; PP SEBS BLENDS; TERNARY COMPOSITES; TENSILE PROPERTIES; PHASE-STRUCTURE; HYBRID COMPOSITES; FRACTURE-TOUGHNESS